Use of Extracellular Matrix Cartilage Allograft May Improve Infill of the Defects in Bone Marrow Stimulation for Osteochondral Lesions of the Talus. Issue 1 (January 2022) - Azam, Mohammad; Shimozono, Yoshiharu; Williamson, Emilie; Mercer, Nathaniel P.; Hurley, Eoghan T.; Huang, Hao; Deyer, Timothy; Kennedy, John G.
Category: Ankle Introduction/Purpose: The purpose of this study is to evaluate the effectiveness of Extracellular Matrix Cartilage Allograft (EMCA) as an adjuvant to bone marrow stimulation (BMS) compared to BMS alone in the treatment of osteochondral lesions of the talus (OLT). Methods: A retrospective cohort study comparing patients treated with BMS with EMCA (BMS-EMCA group) and BMS alone (BMS group) between 2013 and 2019 was undertaken. Clinical outcome was evaluated with the Foot and Ankle Outcome Score (FAOS) pre-and postoperatively. Postoperative MRIs were evaluated using a modified Magnetic Resonance Observation of Cartilage Tissue (MOCART) score. Comparisons between groups were made with the Man-Whitney U test for continuous variables and the χ2 or Fisher exact test for categorical variables. Results: Twenty-four patients underwent BMS with EMCA (BMS-EMCA group) and 24 patients underwent BMS alone (BMS group). The mean age was 40.8 years (range, 19 to 60 years) in BMS-EMCA group and 47.8 years (range, 24 to 60 years) in BMS group (p=0.060). The mean follow-up time was 20.0 months (range, 12-36 months) in BMS-EMCA group and 26.9 months (range, 12 to 55 months) in BMS group (p=0.031). Both groups showed significant improvements in all FAOS subscales. No significant differences between groups were found in all postoperative FAOS. The mean MOCART score in BMS-EMCA group was higher (76.3 vs 66.3), but not statistically significant (p=0.176). The MRI analysis showed that 87.5% of BMS-EMCA group had complete infill of the defect with repair tissue, however less than half (46.5%) of BMS group had complete infill (p=0.015). Conclusion: BMS with EMCA is an effective treatment strategy for the treatment of OLT and provides better cartilage infill in the defect on MRI. However, this did not translate to improved functional outcomes compared with BMS alone in the short-term.